1987
DOI: 10.1002/hep.1840070123
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of random sample urine bile acids corrected by creatinine in liver disease

Abstract: Bile acids, in a random sample of urine, discriminated normal controls from liver disease, with a probability similar to fasting plasma bile acids (p less than 0.01 and p less than 0.001, depending on the analytical technique). A high degree of correlation between urinary and plasma bile acids (up to r = 0.93) was achieved only when the urine flow was corrected by using a urinary bile acids/creatinine ratio but not with urinary bile acids as simple volume concentration. These findings originated from 10 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
4

Year Published

1988
1988
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 21 publications
0
30
0
4
Order By: Relevance
“…First, although urinary BA analysis is not performed in the laboratories of most hospitals, it should be included in routine investigational assays of chronic cholestatic patients, as expanded lists of phenotypic and metabolic defects associated with IEBAM have been recently reported (30). In clinical practice, urine sample collection is easy to perform, the data are not affected by fasting conditions after correction by Cre, and analyses have low variability and high stability compared with analyses of serum BAs levels (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…First, although urinary BA analysis is not performed in the laboratories of most hospitals, it should be included in routine investigational assays of chronic cholestatic patients, as expanded lists of phenotypic and metabolic defects associated with IEBAM have been recently reported (30). In clinical practice, urine sample collection is easy to perform, the data are not affected by fasting conditions after correction by Cre, and analyses have low variability and high stability compared with analyses of serum BAs levels (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…11 Similarly, specific markers of liver injury have been proposed, for example, urinary levels of bile acids have been proposed as non-invasive markers of minor liver dysfunction which are as sensitive as serum measurements. 32 Elevations in the levels of urinary taurine have also been associated with liver dysfunction. 27,33 However, many endogenous metabolites, such as taurine, fluctuate in concentration as a result of normal physiological variation.…”
Section: Nmr Based Metabonomicsmentioning
confidence: 99%
“…Urine bile acids (UBA) have been detected in patients with hepatic disease since the 1950s (Rudman and Kendall, 1957; Makino et al et al., 1976;Almé et al, 1977;Simko et al, 1987;Batta et al, 1989; Shoda et al acids has been carried out mainly by gas or liquid chromatography -mass spectrometry (GC-MS, LC-MS) in recent studies. GC-MS and LC-MS can identify various structurally different bile acids precisely, and alteration of the composition of UBA can be analyzed.…”
Section: Original Articlementioning
confidence: 99%
“…Normalized UBA values were expressed in micromoles per gram of creat--atinine, because this method was generally used in order to normalize the amount of urinary compounds, and several studies revealed that this normalization was suitable for UBA analysis in human, cats, and dogs (Simko et al, 1987;Trainor et al, 2003;Balkman et al, 2003).…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation